Shoot development in Quercus suber L. somatic embryos - Gonzalez-Benito, M Elena; García-Martín, Gemma; Antonio Manzanera, José (In Vitro Cellular & Developmental Biology - Plant, 2002)
N 6 -Benzyladenine (BA; 0.04–4 mM) application to germinated Quercus suber somatic embryos considerably increased caulinar apex elongation frequency and maintained active growth in the plantlets, although it did not have a signiﬁcant effect on the percentage of shoots with normal morphology. The addition of 0.5 mM indoleacetic acid together with the cytokinin did not have any effect. The use of a low concentration (0.04mM) of BA allowed the appropriate radicle elongation in all germinating somatic embryos, but higher concentrations arrested this elongation.
Keywords: Cork oak; growth regulators; in vitro; plantlet.